A dynamic business framework aimed at guiding South African small businesses towards sustainability by considering Industry 4.0 and Industry 5.0 trends and technologies. - Nel, Bianca (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEM)--Stellenbosch University, 2024.